KEGIATAN MAGANG / LATIHAN KERJA BAGI MAHASISWA - Daryanto Daryanto (Khazanah Pendidikan, 2009)
This research is aimed at finding out 1) the apprenticeship procedure in the Bank of Indonesia and 2) the students’ activity during the apprenticeship. The object of the research was the activity during the apprenticeship as done by the students of the Department of Indonesian Language and Literature of General Soedirman University Purwokerto. There were six student as the subject of research. The result showed there were eight stages in the whole activity of apprenticeship. They were assigned to work in the library, Archiving, and Human Resource Unit. Key words: archiving unit, apprenticeship, library unit, human resource unit